State-of-the-Art of Eggshell Waste in Materials Science: Recent Advances in Catalysis, Pharmaceutical Applications, and Mechanochemistry - Baláž, Matej; Boldyreva, Elena V.; Rybin, Dmitry; Pavlović, Stefan; Rodríguez-Padrón, Daily; Mudrinić, Tihana; Luque, Rafael (Frontiers in Bioengineering and Biotechnology, 2021)
Eggshell waste belongs among the most abundant waste materials coming from food processing technologies. Despite the unique properties that both its components (eggshell, ES, and eggshell membrane, ESM) possess, it is very often discarded without further use. This review article aims to summarize the recent reports utilizing eggshell waste for very diverse purposes, stressing on the need of using a mechanochemical approach to broaden its applications. The most studied field with regards to the potential use of eggshell waste is catalysis. Upon proper treatment, it can be used for turning waste oils into biodiesel. The catalytic effect of eggshell-based material in the organic synthesis is also very beneficial. In inorganic chemistry, the eggshell membrane is very often used as a templating agent for the nanoparticles production. Such composites are suitable for the application in photocatalysis. These bionanocomposites are also capable of heavy metal ions reduction and can be also used for the ozonation process. The eggshell and its membrane are applicable in electrochemistry as well. Due to the high protein content and the presence of functional groups on the surface, ESM can be easily converted to a high-performance electrode material. Finally, both ES and ESM are suitable for medical applications, as the former can be used as an inexpensive Ca2+ source for the development of medications, particles for drug delivery, organic matrix/mineral nanocomposites as potential tissue scaffolds, food supplements and the latter for the treatment of joint diseases, in reparative medicine and vascular graft producing. For the majority of the above-mentioned applications, the pretreatment of the eggshell waste is necessary. Among other options, the mechanochemical pretreatment has found an inevitable place. Since the publication of the last review paper devoted to the mechanochemical treatment of eggshell waste, a few new works have appeared, which are reviewed here to underline the sustainable character of the proposed methodology. The mechanochemical treatment of eggshell is capable of producing the nanoscale material which can be further used for bioceramics synthesis, dehalogenation processes, wastewater treatment, preparation of hydrophobic filter, lithium-ion batteries, dental materials and in building industry as cement.